2016
DOI: 10.1038/srep32841
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous spatiotemporal mapping of in situ pH and bacterial activity within an intact 3D microcolony structure

Abstract: Biofilms are comprised of bacterial-clusters (microcolonies) enmeshed in an extracellular matrix. Streptococcus mutans can produce exopolysaccharides (EPS)-matrix and assemble microcolonies with acidic microenvironments that can cause tooth-decay despite the surrounding neutral-pH found in oral cavity. How the matrix influences the pH and bacterial activity locally remains unclear. Here, we simultaneously analyzed in situ pH and gene expression within intact biofilms and measured the impact of damage to the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 50 publications
(94 reference statements)
4
80
0
Order By: Relevance
“…Consequently, the metabolism of intracellular and extracellular polysaccharides can promote a greater susceptibility to dental caries by prolonging the exposure of tooth surfaces to organic acids. In other words, there is an upregulation mechanism for dental demineralization and consequently a constant generation of acidic pH niches [22][23][24] . With regard to the CF group, and according to the latter-mentioned hypothesis, the increase in the salivary calcium concentration after sucrose rinse can be explained by the low basal metabolism of the biofilm in CF individuals, which is forced to increase the sucrose metabolism and ultimately shift the ionic imbalance at the interface tooth-biofilm-saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the metabolism of intracellular and extracellular polysaccharides can promote a greater susceptibility to dental caries by prolonging the exposure of tooth surfaces to organic acids. In other words, there is an upregulation mechanism for dental demineralization and consequently a constant generation of acidic pH niches [22][23][24] . With regard to the CF group, and according to the latter-mentioned hypothesis, the increase in the salivary calcium concentration after sucrose rinse can be explained by the low basal metabolism of the biofilm in CF individuals, which is forced to increase the sucrose metabolism and ultimately shift the ionic imbalance at the interface tooth-biofilm-saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Both factors can influence the diffusion of metabolites and how antimicrobial agents reach the microorganisms. In previous studies, it was demonstrated that inside large microcolonies, acidic niches can be created that could promote tooth demineralization (Xiao et al 2012; Hwang et al 2016). The lack of distinct microcolonies could be due to the influence of S. gordonii and A. naeslundii on the construction and assembly of the 3-D structure of microcolonies, such that the EPS is spread across the biofilm and not concentrated at specific areas, appearing as a carpet-like morphology rather than the ‘peaks and valleys’ observed in single-species biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…1). This film protects the mineralized surface of teeth from erosion by acids in the diet or acids produced by oral bacteria, the latter being a first step in the initiation of dental caries [6365]. The lubricating effect of glycosylated mucins also protects the integrity of the tooth occlusal surfaces from attrition through antagonistic teeth and excessive wear through abrasive food components.…”
Section: Host-derived Innate and Immune-related Compounds In Human Samentioning
confidence: 99%